The Influence Of Content Marketing on Consumer Purchase Intention (Study on TikTok @otsky_official in Indonesia) - Romualdus Domu Sinaga; Roslina (International Journal of Economics, Business and Innovation Research, 2026)
The rapid growth of short form video based social media platforms, particularly TikTok, has transformed digital marketing practices through content marketing strategies. This study aims to examine the effect of content marketing on consumer purchase intention, measured through the dimensions of reliability, disbelief, and persuasion knowledge, on the TikTok account @otsky_official in Indonesia. This research adopts a quantitative approach using a survey method. Data were collected through an online questionnaire distributed to 168 TikTok users who had viewed or interacted with content from @otsky_official, selected using non-probability sampling with a purposive sampling technique. The data were analyzed using multiple linear regression with SPSS. The results indicate that reliability has a positive and significant effect on purchase intention, disbelief has no significant effect on purchase intention, and persuasion knowledge has a positive and significant effect on purchase intention. These findings suggest that the effectiveness of content marketing on TikTok is influenced by the perceived credibility of information, the level of consumer skepticism, and consumers’ awareness of persuasive intent embedded in marketing content.